2014
DOI: 10.1002/pca.2540
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted Extraction of Gymnemic Acids from Gymnema sylvestre Leaves and its Effect on Insulin‐producing RINm‐5 F β Cell Lines

Abstract: Response surface methodology was successfully used to improve the extraction of gymnemic acids from G. sylvestre leaves. The ultrasound-assisted extraction process may be a better alternative to prepare such herbal extracts because it saves time and may prevent excess degradation of the target analytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Taken together, the bioactive compounds present in Gymnema sylvestre could be a possible reason for better adherence and proliferation of the hDFs and HaCaT. The major bioactive compounds present in Gymnema sylvestre extracts were gymnemic acids and gymnemagenin [59,60,61]. The other phytoconstituents from Gymnema sylvestre reported were kaempferol, quercetin [62], triterpenoid saponin [63], lupeol and stigmasterol [64].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the bioactive compounds present in Gymnema sylvestre could be a possible reason for better adherence and proliferation of the hDFs and HaCaT. The major bioactive compounds present in Gymnema sylvestre extracts were gymnemic acids and gymnemagenin [59,60,61]. The other phytoconstituents from Gymnema sylvestre reported were kaempferol, quercetin [62], triterpenoid saponin [63], lupeol and stigmasterol [64].…”
Section: Resultsmentioning
confidence: 99%
“…29 Various studies have verified that GA plays an important role in the treatment of T2DM, although the mechanism responsible for its antihypoglycemic effects has not been studied. 30,31 Based on previous studies, we chose the doses of 40 and 80 mg/kg/day to investigate the potential antidiabetic effects of GA in T2DM rats. The results showed that 6 weeks of treatment with GA alleviated the diabetic symptoms as evidenced by reduced FBG and insulin levels and HbA1c ratio.…”
Section: Discussionmentioning
confidence: 99%
“…From previous findings, it is reported that fermentation of G. sylvestre leaves showed better activity as compared to natural extract . Gymnemic acid is the major bioactive constituent, and it easily converted into gymnemagenin.…”
Section: Resultsmentioning
confidence: 96%
“…The heated solution cooled and extracted with chloroform. The chloroform extract was concentrated to get gymnemagenin . While the methanolic solution of extract and fermented materials were also used for HPTLC analysis.…”
Section: Methodsmentioning
confidence: 99%